If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x=5(2x-7)
We move all terms to the left:
4x-(5(2x-7))=0
We calculate terms in parentheses: -(5(2x-7)), so:We get rid of parentheses
5(2x-7)
We multiply parentheses
10x-35
Back to the equation:
-(10x-35)
4x-10x+35=0
We add all the numbers together, and all the variables
-6x+35=0
We move all terms containing x to the left, all other terms to the right
-6x=-35
x=-35/-6
x=5+5/6
| 8x-4=7x-4 | | 7x-2=7-2x | | 5=5y+10 | | 11n-7=37 | | |5x+7|+13=26 | | (3+5x)+4=4 | | 5x-7=4×+3 | | 3(x+7=42 | | 18+(7x²-5)=1 | | 1x/2+9=14 | | 0=x^2-6x+4x-9 | | 2y²-50=0 | | 8x+4/3x=2 | | 20x/8=5 | | n/20+6=35 | | 2x2-12x+20=0 | | 5÷q=10 | | n/5+2=15 | | Y=2E+08x+404676 | | 10×x÷6-3+16=26 | | 2y=y|5+8 | | 180=x+10+x+x+120 | | 180=x+10+x+x×120 | | x^2+9√x+14=0 | | 9x²+17=1 | | Xx2+50=xx5-13 | | 180=130+x+60+x | | (4x+5)2=90 | | 9x+3=-7 | | 4x^2-15x-250=0 | | 13=x/10+3 | | 4=b/6-6 |